Effect of age on seed digestion in parrots (Amazona aestiva) - Vendramin-Gallo, M.; Pessutti, C.; Pezzato, Antonio Celso [UNESP]; Vicentini-Paulino, MLM (Univ Chicago Press, 2001)
The objective of this study was to compare the capacity of adult (more than 3 yr old) and young (less than 1 yr old) true parrots to digest seeds that are normally included in their diet in captivity, particularly soybean, sunflower, and corn. All the seeds were offered for 5 d with an interval of 15 d between different diets. The seeds of soybean and corn were boiled for 15 min and soaked in water at ambient temperature for 12 h before being fed to the birds. There were no differences in the digestibilities of crude protein and fats (ether extract) among animals, but the digestibilities of dry matter and crude fiber by the adult animals were higher than those of the young ones. The digestibility of carbohydrate (nitrogen-free extract) by adult birds was higher only for sunflower seeds. It is concluded that the capacity of parrots to digest fiber may change according to the age of the animal. Since the digestion of fiber depends on the action of microorganisms, these results suggest that the colonization of the gastrointestinal tract is delayed or very slow in young parrots.